A transposição do ensino presencial para o ensino remoto emergencial sob o enfoque ergo-dialógico : dramáticas de usos de si e excedente de visão do professor do ensino básico público - Voges, Márcia Cristina Neves (2023)
This study discusses the complexity of the teaching activity by proposing reflections on face-to-face work, emergency remote teaching (ERE in portuguese) and the dramatics of the use of self faced by teachers of public education during the COVID-19 pandemic (SARS-CoV-2), in 2020. Thus, this doctoral research explores language and work in the pandemic context, which intertwine the interfaces postulated by Bakhtin Circle's theories and by the ergological studies. Based on these principles, the reasearch question is: what are the evaluative aspects of the teaching profession that emerge from teachers' verbalizations about the transposition of face-to-face teaching to ERE and that can reveal the resignification of themselves related to the professional activity? The main objective of the present study is to give voice to teachers about the teaching activity from the perspective of experiences in the ERE, and from these experiences propose reflections and refractions that can contribute to the understanding of the profession in the pandemic context and of future professional re-elaborations of themselves - of teachers. This objective unfolds into the following specific objectives: a) to investigate the impact of COVID-19 pandemic in teachers of public education in order to bring to discussion the impasses faced during the transposition of face-to-face teaching to ERE; b) identify the dialogic relations and the aspects of industrious activity of teachers, between doing and being, under the tension of the transposition from face-to-face teaching to ERE and its implications in the use of technologies and in the adaptation to the new teaching modality, or in personal challenges and/or in the imposed by educational and health institutions; c) verify the dramatics of the use of self in the face of teacher's activities in the development of students' essential skills and abilities during the ERE context, considering the clashes and tensions with what is prescribed. For the elaboration of these objectives, this study is based on the dialogical perspective of language and on the ergological approach to work in order to contemplate language manifestations in interaction with work practices. This theoretical-methodological basis, supported by the ergo-dialogical approach, in addition to providing access to the uniqueness of human work activity through ergology, entails, in the light of Bakhtinian theory, that the meeting of two value centers — the self and the other — , filled with experiences and historicities, and different ways of life understandings, is engendered in the social horizon that surrounds them and in the universe in which they are inserted. Therefore, these value centers, even if they are close, will always be different. From a methodological perspective, individual interviews consisting of ten questions were conducted with four teachers through Google Meet. The subjects of this research are, therefore, four teachers of public education who teach specifically Portuguese in state schools in the capital of Rio Grande do Sul, Porto Alegre. The thesis defended is that the different uses of teacher's self (by themselves and by the other) intensify the excess of seeing in the re-elaborations and resignifications of themselves and of the teaching profession, considering the work performed in home office during the pandemic context. As a result of this investigation, it is understood that the process of the transposition from face-to-face teaching to a remote teaching environment reverberated substantial dialogic constructions that allow to comprehend how the teaching work in the pandemic context took place, since in the verbalizations these constructions reflect and refract the teachers' work re-elaborations and resignifications, as well as provide paths to (trans)form the teaching for new generations to come.